A bispecific circular aptamer tethering a built-in universal molecular tag for functional protein delivery. Issue 35 (1st September 2020) - Pan, Xiaoshu; Yang, Yu; Li, Long; Li, Xiaowei; Li, Qiang; Cui, Cheng; Wang, Bang; Kuai, Hailan; Jiang, Jianhui; Tan, Weihong
Abstract : A bispecific circular aptamer was utilized to tether a built-in His tag to specific cells to enhance the delivery of functional proteins. Abstract : Chemically engineering endogenous amino acids with a molecular tag is one of the most common routes of artificially functionalizing proteins for identification or cellular delivery. However, it is challenging to make conjugation efficient, facile and productive as well as avoiding a high chance of deactivation of the functional proteins. Here we present a new and straightforward design to specifically tether the distinct six polyhistidine tag, terminally expressed on protein cargoes and cellular membrane proteins by using bispecific circular aptamers (bc-apts). The anti-His tag aptamer on one end of the bc-apt can easily recognize the biorthogonal six polyhistidine tag (His tag) on functional proteins like EGFP or RNase A. Meanwhile, a cell-specific aptamer, sgc8, on the other end efficiently facilitates the targeted delivery of functional proteins, improving their overall bioactivity in the cellular milieu by around 4 fold. Therefore, the nuclease-resistant bc-apt is a promising molecular tethering reagent to enable the noncovalent crosslink between live diseased cells and His tag protein cargoes.